Telling the story: a study in the segregation of women prisoners - Martel, Joane (Social justice, 2001)
Part of a special issue on welfare and punishment in the era of President George W. Bush. A study was conducted to create a knowledge base to counter the lack of studies on women segregated in prison, as well as the general absence of experimentally-based research on penology. Data were drawn from documenting experiences of segregation of 12 women prisoners in the Canadian Prairies. Findings indicate that the segregation of women prisoners leaves them with a precarious self-image and fatalistic attitudes about being able to overcome this image; in essence, segregation accentuates the marginalization of these women and perpetuates it beyond their time of segregation.